Teaching Writing By Using Synergetic Teaching Strategy To The Eighth Grade Students Of Smp Negeri 3 Lubuklinggau - Ardayati Ardayati (Universitas Mathla'ul Anwar Banten, 2017)
This research aimed to find out whether or not it is significantly effective to teach writing by using synergetic teching strategy to the eighth grade students of SMPN 3 Lubuklinggau. Method used was pre-experimental. The data was analyzed through four techniques: individual score, minimuntuum mastery criteria, normality testing, mtched t-test calculation. Therefore, the null hypotheses (H0) was rejected and the alternative hypotheses (Ha) was accepted. It can be concluded that it was significantly effective to teach writing by using synergetic teaching strategy to the eighth grade students of SMPN 3 lubuklinggau.